A Square‐Planar Complex of Platinum(0). Issue 49 (9th November 2016) - Takeuchi, Katsuhiko; Taguchi, Hiro‐omi; Tanigawa, Ippei; Tsujimoto, Shota; Matsuo, Tsukasa; Tanaka, Hiromasa; Yoshizawa, Kazunari; Ozawa, Fumiyuki
Abstract: The Pt 0 complex [Pt(PPh3 )(Eind2 ‐BPEP)] with a pyridine‐based PNP‐pincer‐type phosphaalkene ligand (Eind2 ‐BPEP) has a highly planar geometry around Pt with ∑(Pt)=358.6°. This coordination geometry is very uncommon for formal d 10 complexes, and the Pd and Ni homologues with the same ligands adopt distorted tetrahedral geometries. DFT calculations reveal that both the Pt and Pd complexes are M 0 species with nearly ten valence electrons on the metals whereas their atomic orbital occupancies are evidently different from one another. The Pt complex has a higher occupancy of the atomic 6s orbital because of strong s–d hybridization due to relativistic effects, thereby adopting a highly planar geometry reflecting the shape and orientation of the partially unoccupied d x 2 - y 2 orbital. Abstract : Unusual coordination geometry : A platinum(0) complex with a PNP‐pincer‐type phosphaalkene ligand adopts a highly planar geometry around platinum, which is very uncommon for formal d 10 complexes. DFT calculations indicate that the planar structure is tightly linked with strong s–d hybridization due to relativistic effects.